La industria del autotransporte de pasajeros y sus beneficios tributarios - Gutiérrez Medrano, Benito (Universidad Michoacana de San Nicolás de Hidalgo, 2021)
The passenger motor transport industry must comply with its fiscal obligations the same as all Mexicans, but unlike many other Mexicans, taxpayers who engage in the activity of passenger motor transport, in addition to the fiscal incentives generally established for All taxpayers, this sector specifically enjoys a series of tax benefits that allow them to save money in paying their taxes, but many taxpayers to whom these benefits are applied are unaware of them and therefore do not apply them, resulting in a higher tax payment. Therefore, it is necessary to have knowledge of the laws applicable to the passenger motor transport sector in order to correctly comply with their respective obligations, but also to know the rights and benefits that are applicable to them. Fiscally, it is extremely important that the laws applicable to the sector are known in order to correctly comply with the payment of the taxes to which one is bound, but it is also necessary to know the other legal provisions to know the tax benefits applicable to said sector, such as They are the Income Tax Law, the Federation Income Law and the Administrative Facilities Resolution. In such a way that once the legal provisions mentioned above have been analyzed, we will be able to know the tax incentives for diesel, booths, as well as those established in administrative facilities, and with their correct application, achieve a decrease in the tax burden. If taxpayers from other economic sectors wanted to have these fiscal incentives, but do not have them, it would be incredulous that those who had them, did not apply them due to their ignorance.

La industria del autotransporte de pasajeros debe de cumplir con sus obligaciones fiscales igual que todos los mexicanos, pero a diferencia de muchos otros mexicanos, los contribuyentes que se dedican a la actividad del autotransporte de pasajeros, además de los estímulos fiscales establecidos de manera general para todos los contribuyentes; este sector, específicamente goza de una serie de beneficios tributarios que les permite un ahorro económico en el pago de sus impuestos, pero muchos contribuyentes a quienes les aplican estos beneficios los desconocen y por lo tanto no los aplican, teniendo como consecuencia un mayor pago de impuestos. Por lo tanto, es necesario que se tenga el conocimiento de las leyes aplicables al sector del autotransporte de pasajeros a fin de cumplir correctamente con sus respectivas obligaciones, pero también para conocer los derechos y beneficios que les son aplicables. Fiscalmente es de suma importancia que se conozcan las leyes aplicables al sector para poder cumplir correctamente con el pago de los impuestos a que se esté obligado, pero también es necesario conocer las demás disposiciones jurídicas para conocer los beneficios tributarios aplicables a dicho sector, como lo son la Ley del Impuesto Sobre la Renta, la Ley de Ingresos de la Federación y la Resolución de Facilidades Administrativas. De tal manera que una vez analizadas las disposiciones jurídicas comentadas anteriormente estaremos en posibilidades de conocer los estímulos fiscales al diésel, a las casetas, así como los establecidos en las facilidades administrativas, y con su correcta aplicación lograr una disminución de la carga tributaria. Si contribuyentes de otros sectores económicos quisieran tener estos estímulos fiscales, pero no los tienen, resultaría ilógico que los contribuyentes que los tienen, no los aplicaran por el desconocimiento de los mismos.
Facultad de Contaduría y Ciencias Administrativas. Maestría en Fiscal
Keywords: info:eu-repo/classification/cti/5; FCCA-M-2021-0303; Obligaciones fiscales; Impuestos; Estímulos fiscales; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/6204